Future research directions to identify risks and mitigation strategies for neurostructural, ocular, and behavioral changes induced by human spaceflight: A NASA-ESA expert group consensus report - Seidler, Rachael D.; Stern, Claudia; Basner, Mathias; Stahn, Alexander C.; Wuyts, Floris L.; zu Eulenburg, Peter (Frontiers in Neural Circuits, 2022)
A team of experts on the effects of the spaceflight environment on the brain and eye (SANS: Spaceflight-Associated Neuro-ocular Syndrome) was convened by NASA and ESA to (1) review spaceflight-associated structural and functional changes of the human brain and eye, and any interactions between the two; and (2) identify critical future research directions in this area to help characterize the risk and identify possible countermeasures and strategies to mitigate the spaceflight-induced brain and eye alterations. The experts identified 14 critical future research directions that would substantially advance our knowledge of the effects of spending prolonged periods of time in the spaceflight environment on SANS, as well as brain structure and function. They used a paired comparison approach to rank the relative importance of these 14 recommendations, which are discussed in detail in the main report and are summarized briefly below.